Social conflict in post-apartheid South Africa : a case study of the conflict at Volkswagen South Africa Ltd. between 1999 and 2000 - Cramer, Josef Wilhelm Peter Maria (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2002.